Determinan Kepatuhan Masyarakat Urban pada Protokol Kesehatan dalam Mencegah Penyebaran Covid-19 di Era Kebiasaan Baru - Nayla Kamilia Fithri; Rizki Amalia; Diah Tika Anggraeni (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: The COVID-19 pandemic has changed the way of life. We are facing new challenges, including how to carry out daily life while still making efforts to prevent the spread of the Covid-19 virus. The implementation is to implement the health protocol as much as possible.  However, we still do not know much about the rate and determinants of adoption of the recommended health behaviors. Objective: The research objective was to determine the factors that affect public compliance with the Covid-19 health Protokol. Method: The method used in this research is to use a descriptive analytical survey research type with a cross-sectional approach. he population in this study were all people with a sample size of 212 people and were selected using convinience sampling. The data was collected using an online questionnaire for one month. Data analysis used in this study was bivariate analysis using the chi square test. Result: The results showed that there were one factors that had a significant relationship with public compliance with health Protocols, it was attitude (p 0.000), and four factors that had not significant effect on public compliance with health Protokol, namely age (p 0,919), knowlage (p 0,913), gender (p 0.146) and martial status (p 0,900). Conclusion: It is hoped that policy makers can disseminate information about Covid using the  right  media  so  that  it  can  increase interaction   and  attract   participants  in   increasing   knowledge,   attitudes,   motivation  and  public compliance with the Covid-19 health Protokol.